2013
DOI: 10.1371/journal.pone.0074484
|View full text |Cite
|
Sign up to set email alerts
|

Organized Emergence of Multiple-Generations of Teeth in Snakes Is Dysregulated by Activation of Wnt/Beta-Catenin Signalling

Abstract: In contrast to mammals, most reptiles constantly regenerate their teeth. In the snake, the epithelial dental lamina ends in a successional lamina, which proliferates and elongates forming multiple tooth generations, all linked by a permanent dental lamina. To investigate the mechanisms used to control the initiation of new tooth germs in an ordered sequential pattern we utilized the polyphodont (multiple-generation) corn snake (Pantherophis guttatus). We observed that the dental lamina expressed the transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 41 publications
2
68
1
Order By: Relevance
“…Similar to the chondrichthyan and amphibian species studied, the replacing series of tooth germs in polyphyodont squamates are united by a permanent dental lamina linking the developing teeth in a chain to the functional dentition, and the oral surface [10,12,47,48]. At birth 3-4 developing generations of teeth are found linked to the dental lamina, making a developmental series ready to replace the functional tooth.…”
Section: Reptilesmentioning
confidence: 93%
See 2 more Smart Citations
“…Similar to the chondrichthyan and amphibian species studied, the replacing series of tooth germs in polyphyodont squamates are united by a permanent dental lamina linking the developing teeth in a chain to the functional dentition, and the oral surface [10,12,47,48]. At birth 3-4 developing generations of teeth are found linked to the dental lamina, making a developmental series ready to replace the functional tooth.…”
Section: Reptilesmentioning
confidence: 93%
“…The squamate successional lamina is a region of high proliferation and low apoptosis (programmed cell death) [47,56]. Fate mapping of the successional lamina in the snake has shown that the cells in the successional lamina contribute both to the new generations of teeth and are retained at the tip of the lamina [10]. In species that only have one set of teeth the successional lamina forms but stops proliferating, losing its bulge shape.…”
Section: Reptilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reptiles, such as geckos and crocodiles, most toothed fishes and other vertebrates are polyphyodont (Fuenzalida et al 2000;Gaete and Tucker 2013). Most mammals are diphyodont, such as our species, but others (e.g., elephants, kangaroos and manatees) are polyphyodont.…”
Section: Teethmentioning
confidence: 99%
“…The elephant has six dentitions (Shoshani 2000), and alligators can replace up to 50 times their teeth (Wu et al 2013): The number of replacements is specific enough for the duration of their lives. Other species with strong wear have multiple substitutions, unlimited in their number (Fuenzalida et al 2000;Gaete and Tucker 2013), or they exhibit a continuous growth of the teeth as they wear out [e.g., rodents (Single et al 2001)]. …”
Section: Teethmentioning
confidence: 99%